High-performance electromagnetic calorimeter with oriented crystals to open new pathways in particle and astroparticle physics - Bandiera, L.; Fedeli, P. (Frontiers in Sensors, 2025)
Progress in high-energy physics has long relied on electromagnetic calorimeters–total absorption devices used to measure the energy of electrons and photons. Recently, it has been shown that electromagnetic showers can develop more rapidly inside scintillating crystals when the incoming beam is aligned with a crystal axis within a few tenths of a degree. Building on this, we are developing and testing a novel type of calorimeter based on oriented crystals, which enables a significantly reduced depth for containing high-energy showers compared to conventional designs. We report here the full R&D path, from single-crystal studies across various materials to the construction of the first 3×3 matrix of PWO crystals. The angular acceptance for shower acceleration is largely energy-independent, while the shower-length reduction becomes more pronounced at higher energies. This makes oriented-crystal calorimetry a promising solution for next-generation high-performance detectors. In addition to improving particle identification through reduced hadronic sensitivity, this technology is well-suited for forward calorimetry at colliders, fixed-target setups, and beam dumps for light dark matter searches. Furthermore, in γ-ray astrophysics, such compact calorimeters could enhance sensitivity above 1 GeV by increasing effective area without adding weight–ideal for space-based telescopes targeting high-energy transients and multi-messenger events.